2009
DOI: 10.1007/s10162-009-0198-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Fractalkine Receptor CX3CR1 on Cochlear Macrophages Influences Survival of Hair Cells Following Ototoxic Injury

Abstract: The role of innate immunity and macrophage recruitment to the inner ear after hair cell injury is a subject where little is known. In this paper, we demonstrate recruitment of monocytes and macrophages to the inner ear after kanamycin. We also examined the effect of fractalkine receptor (CX3CR1) deletion in kanamycin ototoxicity. We observed more functional and structural damage in CX3CR1 null mice compared to wild-type and heterozygous littermates. In order to determine if increased susceptibility to kanamyci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
116
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(126 citation statements)
references
References 38 publications
8
116
2
Order By: Relevance
“…Prior studies have demonstrated that macrophages are recruited into the cochlea after acoustic trauma (Fredelius and RaskAndersen, 1990;Hirose et al, 2005) or aminoglycoside ototoxicity (Sato et al, 2010). However, it is unclear whether this increase in macrophages was entirely attributable to hair cell death or whether other tissue injury caused by noise or ototoxic insults might also attract macrophages.…”
Section: Dt-induced Hair Cell Ablation Recruits Macrophages To the Damentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have demonstrated that macrophages are recruited into the cochlea after acoustic trauma (Fredelius and RaskAndersen, 1990;Hirose et al, 2005) or aminoglycoside ototoxicity (Sato et al, 2010). However, it is unclear whether this increase in macrophages was entirely attributable to hair cell death or whether other tissue injury caused by noise or ototoxic insults might also attract macrophages.…”
Section: Dt-induced Hair Cell Ablation Recruits Macrophages To the Damentioning
confidence: 99%
“…Macrophages are recruited into the cochlea after acoustic trauma (Fredelius and Rask-Andersen, 1990;Hirose et al, 2005) and aminoglycoside ototoxicity (Sato et al, 2010). However, because both noise and ototoxins can injure multiple cell types within the ear, it was unclear whether the injury-evoked increase in macrophages was caused by hair cell death or by damage to nonsensory tissues of the cochlea.…”
Section: Loss Of Cochlear Hair Cells Is Sufficient For Macrophage Recmentioning
confidence: 99%
See 1 more Smart Citation
“…These effector molecules activated by inflammation are relatively understudied elements of inner ear dysfunction. Mononuclear phagocyte migration into the inner ear, which has been observed in inner ear injury, could play an important role in hearing and balance dysfunction and is accompanied by other inflammatory mediators that affect the short and long term function of the inner ear in the disease state (Hirose et al 2005;Sato et al 2010). In many organ systems, inflammation is accompanied by changes in vascular permeability, and LPS is only one of many ways to stimulate local or systemic inflammation.…”
Section: Systemic Inflammation Induced By Lps Causes Compromise Of Thmentioning
confidence: 99%
“…CX3CR1 GFP/GFP male mice were acquired from The Jackson Laboratory and bred with C57Bl/6 females to produce CX3CR1 GFP/+ mice. These heterozygous mice have been used in previous studies of inner ear macrophages, which indicated that CX3CR1 GFP/+ mice have normal macrophage function in the inner ear and express GFP exclusively in macrophages (Hirose et al 2005;Sautter et al 2006;Sato et al 2008Sato et al , 2010.…”
Section: Cx3cr1 Gfp/+ Micementioning
confidence: 99%